Global solution of reaction diusion system with full matrix - Maroua, Mebarki; Abdelkader, Moumeni (Global Journal of Mathematical Analysis, 2015)
The purpose of this paper is to prove the global existence inÂ time of solutions for the strongly coupled reaction-diffusion system:with full matrix of diffusion coefficients. Our techniques of proof areÂ based on Lyapunov functional methods and some \(L^p\) estimates. we showÂ that global solutions exist. Our investigation applied for a wide class ofÂ the nonlinear terms f and g.